Low-Level Laser Application in the Early Myocardial Infarction Stage Has No Beneficial Role in Heart Failure - Manchini, Martha T.; Antônio, Ednei L.; Silva Junior, José Antônio; de Carvalho, Paulo de Tarso C.; Albertini, Regiane; Pereira, Fernando C.; Feliciano, Regiane; Montemor, Jairo; Vieira, Stella S.; Grandinetti, Vanessa; Yoshizaki, Amanda; Chaves, Marcio; et al. (Frontiers in Physiology, 2017)
Low-level laser therapy (LLLT) has been targeted as a promising approach that can mitigate post-infarction cardiac remodeling. There is some interesting evidence showing that the beneficial role of the LLLT could persist long-term even after the end of the application, but it remains to be systematically evaluated. Therefore, the present study aimed to test the hypothesis that LLLT beneficial effects in the early post-infarction cardiac remodeling could remain in overt heart failure even with the disruption of irradiations. Female Wistar rats were subjected to the coronary occlusion to induce myocardial infarction or Sham operation. A single LLLT application was carried out after 60 s and three days post-coronary occlusion, respectively. Echocardiography was performed three days and at the end of the experiment (five weeks) to evaluate cardiac function. After the last echocardiographic examination, LV hemodynamic evaluation was performed at baseline and on sudden afterload increases. Compared with the Sham group, infarcted rats showed increased systolic and diastolic internal diameter as well as a depressed shortening fraction of LV. The only benefit of the LLLT was a higher shortening fraction after three days of infarction. However, treated-LLLT rats show a lower shortening fraction in the fifth week of study when compared with Sham and non-irradiated rats. A worsening of cardiac function was confirmed in the hemodynamic analysis as evidenced by the lower LV end-diastolic pressure, +dP/dt and -dP/dt with five weeks of study. Cardiac functional reserve was also impaired by infarction as evidenced by an attenuated response of stroke work index and cardiac output to a sudden afterload stress, without LLLT repercussions. No significant differences were found in the myocardial expression of Akt1/VEGF pathway. Collectively, these findings illustrate that LLLT improves LV systolic function in the early post-infarction cardiac remodeling. However, this beneficial effect may be dependent on the maintenance of phototherapy. Long-term studies with LLLT application are needed to establish whether these effects ultimately translate into improved cardiac remodeling.